Think-Pair-Share Technique and Analytic Rubric Assesment for English Writing Learning - Etti (Jurnal Evaluasi Pendidikan, 2017)
This research investigated the application of learning process in learning writing used cooperative learning and rubrics assessment. The finding of the research is Think-Pair-Share (TPS) cooperative learning technique is more effective when followed by analytic rubrics assessment. In variation to that combination, applying TPS cooperative learning with holistic rubric assessment and application of Students’ Team Achievement Division (STAD) learning with analytic rubrics assessment in fact produced positive result of learning. However, this finding needs to be proved through other research to enhance the discovery of the research.